Making natural products from renewable feedstocks: back to the roots?. Issue 3 (18th October 2019) - Kühlborn, Jonas; Groß, Jonathan; Opatz, Till
Abstract : This review highlights the utilization of biomass-derived building blocks in the total synthesis of natural products. Abstract : Covering: up to mid-2019 This review highlights the utilization of biomass-derived building blocks in the total synthesis of natural products. An overview over several renewable feedstock classes, namely wood/lignin, cellulose, chitin and chitosan, fats and oils, as well as terpenes, is given, covering the time span from the initial beginning of natural product synthesis until today. The focus is put on the origin of the employed carbon atoms and on the nature of the complex structures that were assembled therefrom. The emerging trend of turning away from petrochemically derived starting materials back to bio-based resources, just as seen in the early days of total synthesis, shall be demonstrated.